2004
DOI: 10.1074/jbc.m400794200
|View full text |Cite
|
Sign up to set email alerts
|

The DNase-I Binding Loop of Actin May Play a Role in the Regulation of Actin-Myosin Interaction by Tropomyosin/Troponin

Abstract: , on its interaction with myosin S1 in the presence and absence of tropomyosin or tropomyosin-troponin. Both individual modifications reduced activation of S1 ATPase by actin to a similar extent. The effect of ECP cleavage, but not of subtilisin cleavage, was partially reversed by stabilization of interprotomer contacts with phalloidin, indicating different pathways of signal transmission from the N-and C-terminal parts of loop 38 -52 to myosin binding sites. ECP cleavage diminished the affinity to tropomyosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 66 publications
(34 reference statements)
2
12
0
Order By: Relevance
“…Although there are no data supporting direct contact of Tm with Cys 374 of actin (37), the cosedimentation results suggest that the allosteric interaction between Tm and actin was affected by actin glutathionylation. This finding is consistent with the results of prior work suggesting that cooperative binding of Tm to F-actin involved conformational changes propagated along the actin filament subsequent to Tm binding (8,25,38,59). These allosteric changes in actin after Tm binding are supported by cross-linking experiments demonstrating that contact between myosin S1 and actin residues 48 -67 could be abrogated by the presence of Tm (3), despite the absence of direct contact between Tm and actin at these residues (36).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although there are no data supporting direct contact of Tm with Cys 374 of actin (37), the cosedimentation results suggest that the allosteric interaction between Tm and actin was affected by actin glutathionylation. This finding is consistent with the results of prior work suggesting that cooperative binding of Tm to F-actin involved conformational changes propagated along the actin filament subsequent to Tm binding (8,25,38,59). These allosteric changes in actin after Tm binding are supported by cross-linking experiments demonstrating that contact between myosin S1 and actin residues 48 -67 could be abrogated by the presence of Tm (3), despite the absence of direct contact between Tm and actin at these residues (36).…”
Section: Discussionsupporting
confidence: 92%
“…These allosteric changes in actin after Tm binding are supported by cross-linking experiments demonstrating that contact between myosin S1 and actin residues 48 -67 could be abrogated by the presence of Tm (3), despite the absence of direct contact between Tm and actin at these residues (36). In addition, cleavage between residues 42 and 43 of the DNase I binding loop of actin attenuated the inhibitory effect of Tm on actin-activated myosin S1 ATPase activity (38), suggesting that the DNase I binding loop is sensitive to conformational changes subsequent to Tm binding. These data complement data regarding the intermonomer interactions of actin indicating that the DNase I binding loop and the COOH-terminal Cys 374 of the adjacent actin are sufficiently close in proximity to be cross linked efficiently by an ϳ12-Å linker (26).…”
Section: Discussionmentioning
confidence: 83%
“…Previously tropomyosin-dependent cooperativity was assessed by excimer fluorescence of pyrene-labeled tropomyosin [Ishii and Lehrer, 1990;Moraczewska et al, 2004] or S1-induced binding of tropomyosin to actin [Moraczewska et al, 1999;Skórzew-ski et al, 2009b]. In this work, we observed cooperative S1-induced changes in FRET.…”
Section: Discussionsupporting
confidence: 62%
“…Gunning and colleagues [4,5] suggested that the isoforms are driven to their final cellular destinations by affinity of TMs for specific actin structures. Studies on actin modified by site-directed mutagenesis [6–9] or limited proteolysis [10] revealed that the interactions between TM and actin involve direct contacts with charged surface residues as well as allosteric structural transitions within actin itself. It is well established that the affinity of TMs for actin is defined by isoform-specific sequences of TM encoded by alternative exons (reviewed in [1,3]).…”
Section: Introductionmentioning
confidence: 99%